Severe pediatric war trauma: A military-civilian collaboration from retrieval to repatriation. Issue 1 (January 2021) - Samuel, Nir; Epstein, Danny; Oren, Asaf; Shapira, Shachar; Hoffmann, Yoav; Friedman, Nir; Shavit, Itai
Abstract : BACKGROUND: Modern conflicts take a disproportionate and increasing toll on civilians and children. Since 2013, hundreds of Syrian children have fled to the Israeli border. Severely injured children were triaged for military airborne transport and brought to civilian trauma centers in Israel. After recovery, these patients returned to their homes in Syria. We sought to describe a unique model of a coordinated military-civilian response for the stabilization, transport, and in-hospital management of severe pediatric warzone trauma. METHODS: Prehospital and in-hospital data of all severe pediatric trauma casualties transported by military helicopters from the Syrian border were extracted. Data were abstracted from the electronic medical records of military and civilian medical centers' trauma registries. RESULTS: Sixteen critically injured children with a median age of 9.5 years (interquartile range [IQR], 6.5–11.5) were transported from the Syrian border to Level I and Level II trauma centers within Israel. All patients were admitted to intensive care units. Eight patients underwent lifesaving procedures during flight, 7 required airway management, and 5 required thoracostomy. The median injury severity score was 35 (IQR, 13–49). Seven laparotomies, 5 craniotomies, 3 orthopedic surgeries, and 1 skin graft surgery were performed. The median intensive care unit and hospital length of stay were 6 days (IQR, 3–16) and 34 days (IQR, 14–46), respectively. Fifteen patients survived to hospital discharge and returned to their families. CONCLUSION: The findings of this small cohort suggest the benefits of a coordinated military-civilian retrieval of severe pediatric warzone trauma. LEVEL OF EVIDENCE: Therapeutic, Level V.